Creating the curriculum - Wyse, Dominic 1964- (London Routledge, 2013)
"Is there an 'ideal' primary school curriculum? Who should decide what the curriculum is? Should teachers have autonomy over how they teach? The curriculum is the heart of what teachers teach and learners learn: effective teaching is only possible with an effective curriculum. Yet in spite of its importance, there has been a crisis in curriculum that has been caused in large part by governments assuming direct control over the curriculum, assessment, and increasingly, pedagogy. Creating the Curriculum tackles this thorny issue head on, challenging student and practising primary school teachers to think critically about past and present issues and to engage with a new wave of curriculum thinking and development. Considering curriculum construction and its impact on teaching and learning in the four countries of the UK, key issues considered include: - Who should decide the curriculum, its aims and its values - The extent to which issues in primary education swing back and forth - Subjects versus thematic organisation, stages and phases, progression, breadth and balance - Prescription versus teacher autonomy - The key features of effective classroom practice - Strategies for assessing the whole curriculum - How language in the classroom influences curriculum design - Understanding curricula in the context of children's social and personal circumstances - Creativity, curriculum and the classroom Illustrated throughout with strategies and case studies from the classroom, Creating the Curriculum accessibly links the latest research and evidence with concrete examples of good practice. It is a timely exploration of what makes an effective and meanginful curriculum and how teachers can bring new relevance, motivation and powerful values to what they teach"--Provided by publisher.
Contributions by various writers
Keywords: Curriculum planning -- Great Britain; Education, Elementary -- Curricula -- Great Britain